The Influence of Socialization, Income Level, and Tax Sanctions on Taxpayer Compliance in Paying Land and Building Tax in Palu City, Central Sulawesi - Aulia, Eghy Widya Anugrah; Jamaluddin; Usman, Rudy; Tanra, Andi Ainil Mufidah (International Journal of Science and Society, 2025)
Land and Building Tax (PBB in Indonesia) is a tax on land and buildings that contributes to local revenue throughout Indonesia. This study examines the influence of tax socialization, income level, and tax sanctions on taxpayer compliance in paying PBB in Palu City, Central Sulawesi. The research is quantitative with primary data, where 400 repondents were selected with an accidental sampling technique from a population of 142,499 taxpayers. Questionnaires were used to obtain the data, and analyze using Partial Least Square (PLS) method, using WarpPLS version 8.0 software. The novelty of this research lies in the use of a combination of three variables namely socialization, income, and tax sanctions in one analysis model applied specifically to the context of PBB in Palu City, which has never been studied in previous research. The findings reveal that the strength of taxpayer compliance is positively influenced by tax socialization, income, and tax sanctions. The addition this study makes to the literature is to reinforce the theory of tax socialization as the main external propellant of tax compliance as well as to reinforce the result of income level and tax penalties also play an important role in raising local tax compliance. The Palu City Government should continue to strengthen the PBB socialization policy and recommendations policy design PBB-P2 repayment should be conditioned licensing administration so that tax compliance obtained in the future.